2019
DOI: 10.1177/0363546519889038
|View full text |Cite
|
Sign up to set email alerts
|

What Neuromonitoring Changes Can Be Expected During Hip Arthroscopy in the Pediatric Population?

Abstract: Background: As its indications have evolved, hip arthroscopy is now performed more frequently in pediatric patients. However, despite this increase, there is a lack of evidence in the literature about its safety in this population in regard to traction injury of the nerves of the lower extremity. Purpose: To determine neuromonitoring changes of the sciatic, femoral, and obturator nerves during hip arthroscopy in the pediatric population and determine the rate of and risk factors for clinical neurapraxia. Study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“… 1 , 2 , 3 , 4 , 5 , 6 , 7 Previous studies have shown both the duration and magnitude of traction are related to the incidence of traction-related nerve injury. 3 , 8 , 9 Furthermore, some studies suggest the magnitude of traction on the development of traction-related neuropraxias is more important than the duration of traction application. 5 , 10 …”
mentioning
confidence: 99%
“… 1 , 2 , 3 , 4 , 5 , 6 , 7 Previous studies have shown both the duration and magnitude of traction are related to the incidence of traction-related nerve injury. 3 , 8 , 9 Furthermore, some studies suggest the magnitude of traction on the development of traction-related neuropraxias is more important than the duration of traction application. 5 , 10 …”
mentioning
confidence: 99%